2001
DOI: 10.1046/j.0021-8790.2001.00546.x
|View full text |Cite
|
Sign up to set email alerts
|

Butterfly responses to habitat edges in the highly fragmented prairies of Central Iowa

Abstract: Summary1. The behaviour of two butterfly species, a habitat specialist ( Speyeria idalia ) and a habitat generalist ( Danaus plexippus ), was tracked at four prairie edges to determine the extent to which edges act as a barrier to emigration. The four edge types studied were crop, road, field and treeline. The edges differed in structure ranging from highcontrast (treeline) to low-contrast (field). 2. S. idalia , the habitat specialist, responded strongly to all edges, even those with low structural contrast. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
163
2
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(169 citation statements)
references
References 38 publications
3
163
2
1
Order By: Relevance
“…Whether a species persists or invades in such a landscape depends on how individuals move in these patches and how they respond to interfaces between different habitat types. A wealth of data is available on movement behavior in different habitat types (Ries and Debinski 2001;Schultz and Crone 2001;Whittington et al 2005;Reeve et al 2008), and there is a long history of studying habitat selection and patch preference of animals (Rosenzweig 1981;Brown 1988;Fryxell 2008;Beyer et al 2010). Yet there was no modeling framework in place to combine this small-scale information and use it to predict population-scale patterns.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether a species persists or invades in such a landscape depends on how individuals move in these patches and how they respond to interfaces between different habitat types. A wealth of data is available on movement behavior in different habitat types (Ries and Debinski 2001;Schultz and Crone 2001;Whittington et al 2005;Reeve et al 2008), and there is a long history of studying habitat selection and patch preference of animals (Rosenzweig 1981;Brown 1988;Fryxell 2008;Beyer et al 2010). Yet there was no modeling framework in place to combine this small-scale information and use it to predict population-scale patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Schultz and Crone (2001) demonstrated such changes for a prairie butterfly (Icaricia icarioides fenderi) within a patch, outside of a patch, and near edges (see also Crone and Schultz 2008); edge behavior significantly increased residence time in a favorable patch. Ries and Debinski (2001) showed that a habitat specialist (Speyeria idalia) and generalist (Danaus plexippus) butterfly responded differently to different habitat edges and that the specialist returned more frequently to a favorable patch. Reeve et al (2008) characterized movement rates of planthoppers (Prokelisia crocea) in three different habitat types and determined that individuals easily crossed edges between two types but not into unfavorable habitat.…”
Section: Introductionmentioning
confidence: 99%
“…those between meadows with and without the foodplant of a focal species), but not hard boundaries between contrasting habitats (e.g. between meadow and forest) (Ries and Debinski 2001;Ross et al 2005;Haynes and Cronin 2006;Kuefler et al 2010;Eycott et al 2012). In turn, movement patterns in matrix determine emigrant chances of reaching other habitat patches (Crone and Schultz 2008;Eycott et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…between two open habitats) and animals are less likely to move through sharp borders (e.g. between meadow and forest), which could direct the movement along the boundary (Ries and Debinski 2001;Kuefler et al 2010;Eycott et al 2012;Bertoncelj and Dolman 2012). Therefore, it may be expected that corridors are more important for organisms living in landscapes composed of contrasting types of environments, which is the case in the studied system, where tree habitats are embedded in the inhospitable matrix and the beetle is strictly associated with a narrow ecological niche.…”
Section: Discussionmentioning
confidence: 96%